THE CLINICAL SUPERVISION MODEL WITH CLASS ACTION APPROACH OF MICROTEACHING PROGRAM IN THE FKIP OF PGRI MADIUN UNIVERSITY - V Teguh Suharto; Dwi Setyadi; Elly's Mersina Mursidik; Ermi Andriani Meikayanti (Universitas Sebelas Maret, 2018)
Educators have become the main agents in the duty of transfer of knowledge, character building and skill development for the learners to pursue intelligence, good personality, creativity and responsibility for the nation’s welfare. The educators’ role requires the prominent academic, pedagogycal and professional competence. Educators must be capable in designing and developing the proper instruction.To develop the educators’ competence, educational institution needs to provide systematic, effective, and continuous trainings for the teacher candidates through microteaching and apprenticeship programs. Microteaching program enables candidates to practice peer-teaching in the campus, while apprenticeship program makes candidates apply teaching in school classes. The clinical supervision model with class action approach is relevant to characteristics and steps of microteaching program. Professional advice through systematic clinical service after teaching practice can effectively develop candidates’ teaching skill, which motivates candidates to develop themselves in teaching practice.